Earlier sexual debut predicts higher (not lower) levels of father care measured across 12 weeks: an experience sampling study - Corpuz, Randy; Kotov, Daria A.; Donovan, Rylei L. (Frontiers in Psychology, 2023)
Across the lifespan, males negotiate the tradeoff between current and future reproduction. From a life history theory (LHT) perspective, resources invested into earlier reproduction pose a cost to later reproduction. The age of sexual debut is a commonplace measure of sexual maturation. However, in males, thorarche (age of first ejaculation) and years from thorarche to age of first reproduction both represent milestones related to reproductive timing. A fundamental prediction from LHT is that earlier sexual maturation—a “quantity” strategy—predicts decreased levels of care per offspring. In the current study, we test this straightforward relationship looking specifically at a father’s investment of time. In a sample of first-time fathers, we measured the amount of time spent with their 9-to-12-month infants longitudinally using an experience sampling method (ESM)—an ecologically valid method of collecting self-report data on fathers’ use of time Fathers contributed data on their time allocation across a 12-week period. They reported on ages of sexual debut, thorarche, and the years between thorarche and first reproduction (i.e., current age) was calculated. Only age of sexual debut had a relationship with time allocated toward infants. Importantly however, this effect was in a direction opposite of our LHT derived hypothesis. Males with earlier sexual debut spent more time with their infants. Discussion focuses on the potential contributions to this finding and limitations related to small effect size, methods and measurement, and sample demographics.